Older adult health and primary care: autonomy, vulnerabilities and challenges of care - Carneiro, Jeane Lima e Silva; Ayres, José Ricardo de Carvalho Mesquita (Revista de Saúde Pública, 2021)
OBJECTIVE: To understand the relations between autonomy and health-disease-care processes of older adults in the daily life of primary health care. METHODS: Qualitative research developed in 2019, in a primary health unit in the central region of the city of São Paulo, using participant observation and in-depth interviews with 16 health professionals and 8 older adults. The construction and interpretation of the narratives produced in the study were guided by the perspective of Gadamer’s philosophical hermeneutics and Ricoeur’s theory of interpretation. The theoretical framework of vulnerability/Careᵃ, as proposed by Ayres, guided the definition of the study and interpretative categories. RESULTS: Closely related to the difficulties, facilities and strategies to cope with the daily challenges in the health care of older adults, autonomy was an important marker of vulnerability (interpersonal, social and programmatic), indicating areas that require special attention, such as drug dispensing, urban mobility, social isolation, financial frailties and adequacy of service routines. CONCLUSION: Distinctly from an individual attribute, autonomy has proved to be the expression of relational characteristics, requiring plural and flexible practical-moral strategies, techniques and horizons, although always guided by the same ethical commitment to respect the singular needs of individuals.